Improving documentation in prehospital rapid sequence intubation: investigating the use of a dedicated airway registry form. Issue 4 (13th April 2012) - Bloomer, Roger; Burns, Brian J; Ware, Sandra
Abstract : Objective: The quality of medical documentation is integral to audit, clinical governance, education, medico-legal aspects and continuity of patient care. This study aims to investigate the introduction of a dedicated 'Airway Registry Form' (ARF) on the quality of documentation in prehospital rapid sequence intubation. Methods: A retrospective review and comparison of 96 cases predating the introduction of the ARF and 90 cases immediately following its introduction were performed. Results: The introduction of the ARF yielded significant improvement in the recording of selected data points: difficult airway indicators (p<0.0001), Cormack–Lehane grade of laryngoscopy at first attempt (p<0.0001), documentation of confirmation of tracheal intubation with end-tidal carbon dioxide monitoring (p=0.015) and recording of intubator's details (p<0.0001). Conclusions: This study validates the use of a dedicated ARF for the improvement of documentation and data collection related to prehospital rapid sequence intubation when compared with post-event extraction of data from a generic case-record.